Profile of Women receiving Second-trimester Safe Abortion Service at Paropakar Maternity and Women’s Hospital - Shrestha, S.; Dangal, G.; Ghimire, S. (Kathmandu University Medical Journal, 2022)
Background Second trimester abortions account for a small percentage of abortions globally. Abortion is one of the safest medical procedures. Accessibility of safe and high quality second-trimester abortion care can decrease severe complications associated with it. Objective The profile of women undergoing second-trimester abortion was assessed during the study. The profile includes demographic and clinical aspects. The study also aims to find out the rate of surgical and medical methods of abortion and to understand its indications. Method It is a study based on retrospective data collected from charts available at the comprehensive abortion care center at the Paropakar Maternity and Women’s Hospital. The data from Shrawan to Magh 2077 B.S. was collected and calculations were done on MS Excel. Result Higher proportion of women receiving second-trimester abortion were of the age between 21-25 years (n=31; 31%). Most women were literate (n=69; 69%) and n=38(38%) were nulliparous. The most common indication for abortion was maternal mental issues (n=32; 32%). The rate of medical abortion was higher (n=71; 71%) than surgical method of abortion (n=29; 29%). Conclusion There exists both demographic and clinical variations in women undergoing second trimester abortion. Though few women undergo second trimester abortion than first-trimester the variation in profile is significant with most women referring to second trimester abortion due to later diagnosis of pregnancy, women facing financial and logistic barriers to health care, victims of violence and women with pregnancy complications or fetal anomalies.